Lean six sigma in higher education : a practical guide for continuous improvement professionals in higher education - Antony, Jiju (Emerald Publishing Limited, 2020)
This book illustrates the integration of both Lean and Six Sigma as a process excellence methodology which can be utilized in Higher Education environments for achieving and sustaining world class efficiency and effectiveness. It showcases various studies carried out by leading research scholars, academics and practitioners.
Includes index.
Keywords: Universities and colleges -- Administration.; Education -- Higher.; Colleges of higher education.; elektronické knihy; electronic books